How to not lose oneself: the case for relational identity in collaborative supply relationships - Rintala Oskari (Emerald, 2025)
Purpose
For a long time, researchers have stressed the importance of identity for collaborative supply relationships. Accordingly, it has been proposed that supply relationships may be efficiently managed by establishing a shared collective identity among partners. However, this strategy may challenge the partners' individual distinctiveness and thus lead to adversarial relationship outcomes. In this article, it is argued how and when establishing an intergroup relational identity may be a better choice than building a collective identity.
Design/methodology/approach
The conceptual research is based on an analysis of previous literature. Relational identity theorizing and the theory of intergroup leadership are applied to build on and extend previous views on identity in interorganizational contexts.
Findings
It is proposed that when supply chain actors are subject to identity threats in collaborative supply relationships, such threats are driven by the imbalance of power between or among the parties. Therefore, establishing an intergroup relational identity should be preferred over a collective identity in situations characterized by a high identity threat.
Research limitations/implications
Future studies could support this article's theoretical suggestions with empirical evidence.
Practical implications
Intergroup relational identity preserves the distinctiveness of all parties involved in a collaborative relationship and is based on their individual contributions. Managers could support a collaborative environment and promote a shared vision between or among organizations through appropriate rhetoric.
Originality/value
This study contributes to an understanding of the relational aspects of interorganizational behavior by adapting social psychological theories to this area of research.